Theranostic 64Cu-DOTHA2-PSMA allows low toxicity radioligand therapy in mice prostate cancer model - Milot, Marie-Christine; Bélissant-Benesty, Ophélie; Dumulon-Perreault, Véronique; Ait-Mohand, Samia; Geha, Sameh; Richard, Patrick O.; Rousseau, Étienne; Guérin, Brigitte (Frontiers in Oncology, 2023)
We have previously shown that copper-64 (64Cu)-DOTHA2-PSMA can be used for positron emission tomography (PET) imaging of prostate cancer. Owing to the long-lasting, high tumoral uptake of 64Cu-DOTHA2-PSMA, the objective of the current study was to evaluate the therapeutic potential of 64Cu-DOTHA2-PSMA in vivo. LNCaP tumor-bearing NOD-Rag1nullIL2rgnull (NRG) mice were treated with an intraveinous single-dose of 64Cu-DOTHA2-PSMA at maximal tolerated injected activity, natCu-DOTHA2-PSMA at equimolar amount (control) or lutetium-177 (177Lu)-PSMA-617 at 120 MBq to assess their impact on survival. Weight, well-being and tumor size were followed until mice reached 62 days post-injection or ethical limits. Toxicity was assessed through weight, red blood cells (RBCs) counts, pathology and dosimetry calculations. Survival was longer with 64Cu-DOTHA2-PSMA than with natCu-DOTHA2-PSMA (p < 0.001). Likewise, survival was also longer when compared to 177Lu-PSMA-617, although it did not reach statistical significance (p = 0.09). RBCs counts remained within normal range for the 64Cu-DOTHA2-PSMA group. 64Cu-DOTHA2-PSMA treated mice showed non-pathological fibrosis and no other signs of radiation injury. Human extrapolation of dosimetry yielded an effective dose of 3.14 × 10-2 mSv/MBq, with highest organs doses to gastrointestinal tract and liver. Collectively, our data showed that 64Cu-DOTHA2-PSMA-directed radioligand therapy was effective for the treatment of LNCaP tumor-bearing NRG mice with acceptable toxicity and dosimetry. The main potential challenge is the hepatic and gastrointestinal irradiation.